Social Competence of Islamic Education Cluster Teachers in Improving Learning Quality during the Covid-19 Pandemic - Nurfuadi, Nurfuadi; Nurkholis, Nurkholis (Jurnal Edusci, 2024)
This research aims to find out the basic concept of PAI teacher expertise in improving the quality of learning in the Covid-19 era. This research is a qualitative descriptive study, which only describes the social competence of PAI group teachers in improving the quality of learning during the Covid-19 pandemic at Madrasah Aliyah NU Alqur'an Science Sumbang Banyumas and Madrasah Aliyah Negeri 1 Cilacap. The research results show that teachers really need a more mature preparation process regarding the implementation of teaching and learning activity schedules. In connection with the actualization of the social skills of PAI teachers, each teacher forms a communication network between the teacher and students, as well as between teachers and the students' guardians. Teachers' obstacles in the PAI group as an effort to improve the quality of learning in the Covid-19 era are seen from the perspective of students who lack understanding of the teaching material. Another obstacle is related to learning activities which are still mostly theory based so that there is still a lack of applying the material to everyday life. Thus, teachers must motivate students to always learn so that students' understanding of the material increases. As well as thinking about ensuring that learning does not run monotonously, leading to student boredom.